Symbiotic effects of high-pressure acid etching on the oxidation characteristics of coal during coal-and-gas co-mining - Lin Li; Xinyi Chen; Xiangjun Chen; Jishan Liu; Jie Zeng; Chao Pan; Furu Kang; Junwei Yuan; Yunfei Du (Fuel, 2027)

Bruceine D suppressed osteoclast formation via STAT3/NF-κB/NFATc1 signaling and protected postmenopausal osteoporosis - Sisi Lin; Qing Yuan; XinYi Yao; Xin Nie (Molecular Biology Reports, 2026)

Pleasantness shapes congruency effects in odor-induced taste enhancement - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Fulvic acid-iron colloid promotes the migration of As(III) in porous media - Yanhao Li; Youru Yao; Xinyi Wang; Huimin Zhang; Fengman Fang; Yuesheng Lin; Zhiming Zhang; Qing Ji; Jia Yu (Journal of Contaminant Hydrology, 2026)

Intensifying aridity shapes network patterns of soil bacterial communities and geographical distribution of sensitive functional groups in grasslands and farmlands on the Loess Plateau - Jia Wang; Xinyi Guo; Yuru Gao; Kang Zhang; Zhen Yang; Xin Zhao; Jushui Hu; Junyao Deng; Jiaqing Liu; Li Li; Peng Shi; Yanbing Lin; et al. (Applied Soil Ecology, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

Targeted inhibition of JAK2 phosphorylation by GenX disrupts the JAK2-STAT3 pathway and induces cardiovascular toxicity in zebrafish: Insights from network toxicology and molecular dynamics - Yuzhi Zhao; Xiaoqiang Ge; Gaoyuan Wang; Qiaoling Zhang; Chengyu Geng; Zhongxiu Deng; Siyu Chen; Siyue Tan; Yifan Shi; Meng Zhao; Xinyi Wu; Shou-Lin Wang; et al. (Toxicology and Applied Pharmacology, 2026)

BcSak1-mediated adaption to low temperature in Botrytis cinerea represents optional targets for management of cold-tolerant diseases on harvested fruits - Ziwei Su; Yuxuan Lin; Xinyi Long; Jiaxi Zhang; Yin Li; Chuanxi Zhu; Wenjin Yan; Congcong Wang; Yiwen Wang; Junwei Zhao; Xiang Li; Aruppillai Suthaparan; et al. (Postharvest Biology and Technology, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

A biomass asymmetric fabric evaporator based on waste corn stalks for efficient solar evaporation and cogeneration - Mengnan Qu; Xinyi Tian; Jiehui Li; Yuanyuan Wang; Yuhang Gao; Ying Zhang; Zongrui Huang; Lin Liu; Chao Wang; Jinmei He (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal inequities in early-life ecological liveability and sleep health in preschool children - Yongzhou Liang; Hao Pan; Qiyan Chen; Huizhen Li; Xinyi Weng; Mengqiu Cao; Huiyu Zhou; Nahid Mohajeri; Lin Wang; Tianren Yang; Jing Hua (Environmental Pollution, 2026)

NIR-II photoacoustic/Raman multimodal imaging for early detection of arteriovenous fistula fibrosis - Xiaobei Cai; Xinyi Liang; Youyi Zhang; Yaning Qin; Taoxia Wang; Xiaoli Liu; Yuanyuan Qiu; Huan Liu; Lin Jin; Zeyu Xiao; Kai Cui; Guiying Li (Chemical Engineering Journal, 2026)

Multiphysics modeling of coupled hydrogen-glycerol electrolysis for system design and optimization - Lingyu Gao; Fanpeng Ma; Chenhui Wang; Lin Yang; Xinyi Huo; Wei Li; Bingyan Liu; Jiangjiexing Wu; Jinli Zhang (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Synergistic co-culture of Monoraphidium sp. HDMA-20 and HDMA-01 to improve the efficiency of biodiesel production and flax retting wastewater treatment - Xinyi Wang; Meiqi Wang; Boqi Wang; Yimeng Lin; Wenxiang Ping (Biomass and Bioenergy, 2026)

An integrated optimization framework for voyage and fleet allocation planning in Ro-Ro transport under multiple ship types and contract requirements - Chuanzhong Yin; Xinyi Yao; Luoyi Chen; Lin Li; Zi-Ang Zhang (Ocean Engineering, 2026)

Root exudates recruit microbial allies to override their own mobilization effects for cadmium immobilization in intercropped rice - Ye Li; Jie Hou; Mengqi Liu; Hongan Chen; Xinyi Wang; Peizhe Sun; Lin Zhao; Yanpo Yao; Zhaolin Du; Yi An (Journal of Hazardous Materials, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

Go north: Isotope and aDNA analysis reconstructing the life history of a first-generation immigrant in the early Western Zhou Yan state - Xinyi Ouyang; Nina An; Jing Wang; Chen Duan; Yingliang Yang; YiHsien Lin; Chao Ning; Jingning Guo; Xiaohong Wu (Archaeological and Anthropological Sciences, 2026)

PTPRO Governs Synaptic Density, Long-Term Potentiation and Cognitive Function In Vivo - Xiangdong Wang; Jiaguo Wu; Mengna Liu; Kun Zhang; Xinping Yuan; Fangting Xing; Wenjie Xu; Yulin Zheng; Yifei Wu; Lin Luo; Xinyi Ding; Ge Gao; et al. (Neuroscience Bulletin, 2026)

Universal primer-based RPA combined with parallel CRISPR/Cas12a decoding for rapid multi-species meat authentication - Shuang Han; Xinyi Lin; Yuting Lei; Zhen Liu; Jiayang Li; Xueling Ou (Food Chemistry, 2026)

Predictors, sources, and health risks of environmental antibiotic exposure in Chinese pregnant women - Lu Qian; Yi Wang; Sumiao Hong; Yuanping Wang; Haiping Lin; Yuanyuan Chen; Baochang Sun; Yu Liu; Mingxue Wang; Xinyi Zhu; Haozhe Gu; Jiaqi Liu; et al. (Environmental Pollution, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Effects of faba beans ( Vicia faba L.) on the growth, amino and fatty acids compositions, flesh quality and oxidative stability of African catfish, Clarias gariepinus - Qingqing Li; Qifeng Lu; Huai Zhang; Li Lin; Huohong Lv; Xinyi Li (Journal of Fish Biology, 2026)
The African catfish, Clarias gariepinus , is a commercially vital fish that is cultured worldwide, but it often exhibits low‐quality flesh despite high production, which limits its market value. Consequently, there is increasing interest in identifying alternative feed ingredients that can improve flesh quality without severely compromising growth performance. Previous studies have shown that the inclusion of raw faba beans ( Vicia faba L.) in the diet can improve muscle quality in species like tilapia and grass carp by increasing muscle crisped, yet information on their effects in C. gariepinus remains limited. This study aimed to assess the impacts of 0% (Diet I, control group), 40% (Diet II), 50% (Diet III), 60% (Diet IV) and 70% (Diet V) dietary faba beans inclusion on growth performance, physiological parameters and muscle quality of C. gariepinus during 90 days of cultivation. Compared to the control group, C. gariepinus fed faba beans‐containing diets exhibited lower body weight, body weight gain rate (WGR) and specific growth rate (SGR), accompanied by a significant decline in glucose‐6‐phosphate dehydrogenase activity ( p C. gariepinus receiving faba bean‐supplemented diets exhibited a higher density of muscle fibres, broader gaps between fibres and reduced fibre diameter compared with the control group. Fish fed 50% and 60% faba bean diets exhibited significantly greater muscle hardness ( p p C. gariepinus ; however, inclusion levels must be carefully managed because of their adverse effects on growth.

Mitochondrial dynamics in environmental neurotoxicity: beyond oxidative stress toward spatial and functional reorganization - Xinyi Yu; Weiqi Lin; Wenqi Hu; Dingxin Long; Weichao Zhao (Archives of Toxicology, 2026)

Lignin-based porous materials with balanced strength-toughness for highly efficient oil-water separation - Hongwei Yu; Tao Lin; Xinyi Zheng; Jingda Huang; Wenbiao Zhang; Weimiao Lu (Process Safety and Environmental Protection, 2026)

Heading control of a multi-fin biomimetic robotic fish based on Q-learning enhanced central pattern generator (CPG) - Qiyang Zuo; Lin Liang; Xinyi Gao; Yiyang Li; Jiazi Geng; Zhengkun Yi; Feifei Zhang; Kai He; Fengran Xie (Ocean Engineering, 2026)

Construction of unidirectional thermal conducting thermoplastic polyurethane-based foam with continuous gradient structure enables integrated thermal insulation/dissipation functions - Xinyi Liu; Xiaowen Zhao; Lin Ye (Chemical Engineering Journal, 2026)

Efficient self-accelerated degradation of polyester enabled by encapsulated enzymes for closed-loop recycling - Ruiqi Bao; Ning Zheng; Zhenchao Zhou; Tariq Mehmood; Xinyi Shuai; Zejun Lin; Hong Chen (Chemical Engineering Journal, 2026)

Effects of Aluminum Salts on Bacterial Community in Epiphytic Biofilms on Vallisneria Natans Leaves: Characteristics of Nitrogen and Phosphorus Fractions and Bacterial Community Composition - Xue Peng; Xinyi Zhang; Shuxian Zhang; Qingwei Lin; Haokun Zhang; Xiaowen Zhang; Yi Zhang; Steven Jing-Liang Xu; Fred Wang-Fat Lee; Nora Fung-yee Tam; Zhenbin Wu; Biyun Liu (Water, Air, & Soil Pollution, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Source apportionment and source-to-sink relationship of PAHs in surface sediments of complex estuarine environment - Jiawen Yuan; Yali Li; Xinyi Liu; Chongtai Chen; Yongxin Mai; Tian Lin (Applied Geochemistry, 2026)

Deciphering the flavor chemistry of traditional and novel nattos: A multidisciplinary approach integrating amino acid profiling, volatile compound analysis, and molecular docking - Qile Zhang; Jiawei Wu; Yiu Ming Cheung; Yuhong Lin; Xinyi Deng; Minghui Li; Chufeng He; Dianjing Guo; Cheng Li; Hon Ming Lam; Wing Tak Wong (Food and Humanity, 2026)

Effects of low-level lead exposure on hematological parameters and the possible underlying mechanisms - Xiaojing Liao; Tao Lin; Zhaorui Zhang; Peng He; Haimei Wu; Xinyi Ouyang; Qianxi Li; Zihan Yu; Ziyan Zhang; Jiahui Wu; Yingxin Guo; Shanshan Wang; et al. (Environmental Pollution, 2026)

Tetrahydroberberine targets the bcl-2 promoter G-quadruplex to trigger mitochondrial apoptosis and inhibit nasopharyngeal carcinoma progression - Yiyin Long; Bingyi Xiao; Yanhong Hou; Liduan Huang; Xiangyue Hu; Xinyi Liu; Yuxun Lin; Tianfen Xu; Guosheng Tang; Yuqing Wang; Yi Cai (Chemico-Biological Interactions, 2026)

Secondary softening and short-term water quality impacts of dredged sludge-cake used as a substrate for submerged plant restoration: a field experiment - Yichao Wang; Naixi Lin; Yuxing Zhu; Wangxin Li; Xinyi Wang; Tao Sheng; Nuo Chen; Wei Zhu (Environmental Monitoring and Assessment, 2026)

Two-stage tandem co-fermentation of food waste and waste activated sludge assisted by endogenous alkaline hydrolase for short chain fatty acids-oriented biorefinery - Yan Wang; Peixiang Zhang; Jinxuan Liu; Qiao Wei; Jiangbo Ding; Xinyi Li; Jinsuo Lu; Lin Xu; Wenkai Li; Heliang Pang (Journal of Cleaner Production, 2026)

Dual-function tara gum-based antiscalant with efficient antiscaling and antibacterial activity: Performance and molecular simulation investigation - Liping Xiong; Wei Yu; Xinyi Lu; Zhiyu Zhao; Cheng Chen; Renjie Li; Guanhua Jin; Leihong Zhao; Hongjun Lin; Liguo Shen (Journal of Environmental Chemical Engineering, 2026)

A data informativeness evaluation method for grey-box modeling of building thermal dynamics - Xinyi Lin; Zhe Tian; Adrian Chong; Yakai Lu; Jide Niu; Na Deng (Energy and Buildings, 2026)

The synergistic effects of UV-328 and polystyrene microplastics on zebrafish embryos: developmental toxicity, oxidative stress, and neurotoxicity - Xinlu Yang; Xinyi Liao; Lixiang Zhong; Mingfu Lin; Menghuan Zhang; Jun Wang; Yumei Huang (Aquatic Toxicology, 2026)

An efficient embryogenic cell suspension enabling somatic embryogenesis in Phyllostachys edulis - Simeng Kong; Huan Liu; Kaiting Wang; Xiaohong Zhou; Xinyi Yang; Juan Zhuo; Xiangyu Li; Xinchun Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Case report: rapid in vivo resistance mechanism shifts in multiple carbapenem-resistant Pseudomonas aeruginosa strains after esophagectomy in an immunocompromised patient: a case report - Huan Tang; Xinyi Liu; Hai Zhang; Lin Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Spatiotemporal dynamics, source and flux of dissolved black carbon in the monsoon-influenced Yangtze River system - Chongtai Chen; Xinyi Liu; Guopei Huang; Yan Zeng; Tian Lin; Fengchang Wu (Water Research, 2026)

Enhancing taste without salt or sugar: Cross-modal flavor modulation via olfactory cues - Ao Wang; Xinyi Wu; Lin Gao; Qingya Yang; Liuqing Wei; Lingkai Ji; Simin Zhao; Weiping Yang; Mengling Chen; Pei Liang (Food Quality and Preference, 2026)

Natural sources and bioactive mechanisms of anti-inflammatory peptides: from digestive metabolism to bioavailability enhancement strategies - Shengbing Hu; Liwen Liang; Xinyi Peng; Wei Zhang; Wen Li; Jing Deng; Feifei Zhong; Qinlu Lin; Peng Zhou; Jintao He; Feijun Luo; Kilaza Samson Mwaikono (Food Chemistry, 2026)

Periosteum-inspired lightweight aerogel composite for ultrahigh energy dissipation and dynamic impact perception - Qiankun Chen; Jianpeng Wu; Shuai Liu; Xinyi Wang; Shiyu Lin; Purun Wang; Xinglong Gong; Shaolin Ge; Ken Cham-Fai Leung; Shouhu Xuan (Chemical Engineering Journal, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Spatial-temporal patterns and multi-scale drivers of allergenic pollen Fraxinus, Platanus and Humulus in the urban and suburban area of Beijing, China - Xiaoxin Qin; Jianqin Xu; Yiyin Li; Xiao Yun; Hongxing Zhang; Wenjun Liu; Xinyi Zhao; Nan Lin (Urban Forestry & Urban Greening, 2026)

Isolation and identification of Desmodesmus sp. HDMA-07: Nutrient removal and biodiesel production potential in flax fiber wastewater - Han Wang; Xinyi Wang; Boqi Wang; Yimeng Lin; Jingping Ge; Wenxiang Ping (Process Safety and Environmental Protection, 2026)

Topography and rural settlement control the evolution of sloping cropland toward diversity—evidence from the Three Gorges Reservoir Area over half a century - Xinyi Sun; Wenxin Zhao; Yangbing Li; Ying Huang; Lin Liu; Jing'an Shao (Journal of Cleaner Production, 2026)

Development and application of fluorescent immunoassay lateral flow Technology for the Detection of Prolamins in food - Xinyi Zhao; Qi Fu; Wenye Zhu; Hong Lin; Zhiyu Liu; Hao Wang; Phon Reno; Ziye Zhang; Yuhao Huang; Zhenxing Li (Food Chemistry, 2026)

Interplay of habitat heterogeneity and sampling gear in structuring nekton communities: Insights from niche overlap and biomass spectra in a mangrove estuary - Yuming Wang; Xinyi Gao; Jiakang Liu; Yutong Ma; Miaozhi Lin; Tuohui Ye; Jianxiang Feng (Continental Shelf Research, 2026)

Oral cerium-based nanoplatform conjugated with gold to load anti-miR-301a for pH-transited multi-modal therapy of inflammatory bowel disease - Jiafeng Zou; Qingdong Ji; Xier Pan; Yiting Lin; Xinlin Zhao; Xinyi Chen; Liping Yang; Jing Lu; Shuhui Zheng; Zhuo Zhang; Kun Jiang; Feng Gao (Chemical Engineering Journal, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Integrating social media data and machine learning methods for flash flood susceptibility mapping in China - Yaojie Zhuang; Tuoshi Gong; Jian Fang; Dingtao Shen; Weiyu Tang; Sanming Lin; Xinyi Chen; Yihan Zhang (Journal of Hydrology, 2026)

A polysaccharide isolated from sea cucumber intestines enhances immunity and modulates gut microbiota and metabolism with efficacy comparable to that from the body wall - Xinyi Jin; Lin Bai; Chen Song; Jingjing Li; Xiaomeng Ren; Fanhua Kong; Chunqing Ai; Shuang Song (Food Bioscience, 2026)

Apolipoprotein E Deficiency Attenuates Neuroinflammatory Responses and Demyelination in Experimental Autoimmune Encephalomyelitis - Xiaohui Lin; Xilin Wu; Xinyi Guo; Yuqi Zeng; Qinyong Ye; Jian Zhang (Molecular Neurobiology, 2026)

Long-term occupational exhaust fumes exposure and delayed cognitive impairment in older adults: A cross-sectional study in U.S - Lili Liang; Perry E. Sheffield; Rose Saint Fleur-Calixte; Tianxu Xia; Spencer Xinyi Zhang; Jenny J. Lin (NeuroToxicology, 2025)

Groundwater modulates nutrient dynamics in a freshened saltmarsh tidal creek - Jianan Liu; Xueqing Yu; Tong Peng; Xinyi Lin; Jinzhou Du (Marine Chemistry, 2025)

Performance and mechanism of magnetisable-Fe2O3@biochar hydrogel for the removal of organic dyes containing Cr6 + from wastewater - Yonglin Liu; Hanfei Gao; Xinyi Wang; Yifei Wu; Wei Tian; Qingjian Zhang; Baorong Duan; Lin Liu (Journal of Environmental Chemical Engineering, 2025)

Complexation of chitosan-modified porous starch with chlorogenic acid to form ternary gels: Multiscale structural changes and retrogradation behavior - Li Niu; Xiangrui Ren; Hanlin Guan; Xinyi He; Qian Lin; Wenqing Zhao; Wei Liang; Wenhao Li (Food Chemistry, 2025)

Thiol-ene click synthesis of a novel alginate-derived adsorbent: Synergistic adsorption and mechanistic investigation of dye and antibiotic - Xinyi Lu; Wei Yu; Chenglin Ji; Longyufan Liu; Jiaheng Teng; Cheng Chen; Hongjun Lin; Guanhua Jin; Leihong Zhao; Saleem Raza; Liguo Shen (Desalination, 2025)

Construction of high-strength multifunctional flexible sensors based on hydrophobic aggregation phase separation induced by differences in aggregation rate - Jianjun Chen; Xinyi Xiong; Ning Yu; Anqiang Zhang; Yaling Lin (Chemical Engineering Journal, 2025)

Long-term tea cultivation degrades soil health: Insights from microbial structure and function in tea gardens - Xinyi Chen; Mengqi Lin; Zhenghao Wu; Lei Yu; Qingxue Guo (Soil Ecology Letters, 2025)

Submarine groundwater discharge governs dissolved carbon cycling: Multi-scale evidence from a large river-dominated groundwater-saltmarsh-estuary system - Jianan Liu; Liying Lin; Xueqing Yu; Xiaogang Chen; Tong Peng; Xinyi Lin; Xunchi Zhu; Jinzhou Du (Marine Pollution Bulletin, 2025)

Functional analysis of Sf-NPF1 in food intake and antifeedant induction by azadirachtin in Spodoptera frugiperda larvae - Benshui Shu; Yuting Huang; Xinyi Xie; Cuiting Liu; Jintian Lin; Ying Xiao; Jingjing Zhang (Pesticide Biochemistry and Physiology, 2025)

Revealing the characteristic honey-like aroma formation in honey-scented black tea via molecular sensory analysis - Peng Zhang; Weiwei Wu; Bangxing Ma; Changkun Zheng; Qi Lin; Xinyi Zhao; Yan Huang; Fuming Lin; Weijiang Sun (Food Chemistry, 2025)

Platform compounds from lignocellulosic biomass by thermochemical methods: conversion control and chemical insights - Xiuming Jiang; Peilong Li; Zhan Ding; Bingfeng Lin; Xinyi Li (Chemical Engineering Journal, 2025)

Atomic dispersion of scandium in electrochemically reduced copper oxide nanosheets for efficient electrocatalytic CO2 reduction to C2+ products - Yang Zhao; Binwen Zeng; Haoliang Huang; Huanhuan Yang; Zhipeng Yu; Chao Song; Jingwei Wang; Kaiyang Xu; Xinyi Xiang; Wei Wang; Fei Lin; Sheng Meng; et al. (Chemical Engineering Journal, 2025)

Enhancing the theory of planned behavior with social reactive constructs in explaining adolescents’ dietary behaviors - Yongjun Zhou; Xinyi Nie; Yixi Lin; Shasha Pan; Ruohong Cao; Youjie Zhang (Appetite, 2025)

Development of quantum dot-based tetrodotoxin immunochromatographic test strips and the effect of different aquatic product matrices on detection results - Xinyi Zhao; Jinmin Zhang; Wenye Zhu; Hong Lin; Yaqing Wang; Zhenxing Li (Food Control, 2025)

Oxidative stress-mediated neurotoxicity of para-xylene and neuroprotection by gluconolactone in Xenopus laevis - Lu Han; Wenyi Huang; Lingyun Meng; Xinyi Duan; Yufei Wu; Qihui Lin; Xiaohua Wu; Qi Chen; Wanhua Shen (Environmental Pollution, 2025)

Flame-retardant three-dimensional polyvinyl alcohol/microcrystalline cellulose/graphene oxide composite for fire alarm system - Qiuping Wu; Lin Dai; Junjing Ma; Xinyi Wang; Shuangquan Yao; Chengrong Qin; Jianping Sun; Shaohong Shi; Jingru Liu; Zhanhui Yuan; Chuanling Si (Chemical Engineering Journal, 2025)

Control of phosphorus release from sediment by lanthanum carbonate-modified bentonite (LCBT) alone and in combination with Myriophyllum aquaticum: comparison of LCBT with lanthanum-modified bentonite and iron/aluminum co-modified calcite, and efficiency, mechanisms, and environmental safety of LCBT-Myriophyllum aquaticum combination - Xinyi Wang; Jianwei Lin; Yanhui Zhan (Journal of Soils and Sediments, 2025)

Conformational control of Ni coordination sites in pyridyl-functionalized covalent organic frameworks for exceptional CO2 photoreduction - Xinyi Zeng; Meiyan Guo; Lei Wang; Hetao Xu; Chao Lin; Zhipeng Luo; Fengtao Zhang; Shipeng Zhu; Sibo Wang; Yuanxing Fang; Wei Lin; Xiong Chen (Science Bulletin, 2025)

The regulatory role of DELLA protein DkGAI1 in persimmon dwarfism - Xialin Ye; Xinyi Yu; Hongcheng Liu; Xinxin Lin; Xuting Wu; Jiangtao Yu; Shenchun Qu (Plant Science, 2025)

Enhanced numerical simulation and optimization design for large-scale industrial electrolyzers - Lingyu Gao; Chenhui Wang; Lin Yang; Xinyi Huo; Wei Li; Jinli Zhang (Chemical Engineering Journal, 2025)

CRISPR/Cas9 mediated knockout of laccase2 impairs cuticle tanning and pigmentation in the tobacco cutworm, Spodoptera litura - Yingchuan Peng; Yu He; Xinyi Ling; Lin Zeng; Lixia Cao; Lexin Xie; Long Ma; Wanna Zhang; Zhongqiang Jia (Pesticide Biochemistry and Physiology, 2025)

Insight into the enhancement mechanism of repeated freezing-thawing pretreatment promotes carboxymethylation for improving the properties of sweet potato starch: From a multiscale structural perspective - Li Niu; Siwen Yu; Xinyi He; Wei Liang; Qian Lin; Qi Zhao; Xinyu Wang; Ruijie Li; Wenhao Li (Food Chemistry, 2025)

Enhanced phase-transfer kinetics achieved by atomic iron catalysts on hard carbon toward low-temperature sodium-ion batteries - Xinyi Qian; Ziling Wu; Jianan Gu; Yanli Wang; Xiaomin Cheng; Jing Zhang; Hongzhen Lin; Jian Wang; Liang Zhan; Yongzheng Zhang (Chemical Engineering Journal, 2025)

The effects of aerosol on the growth of hydrometeors in deep convective clouds - Xinyi Lin; Qian Chen; Zeyong Zou; Ying He; Chunsong Lu; Zhiliang Shu (Atmospheric Research, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Real-traffic emissions of CO, NOx, CO2, and PM2.5 from vehicles using a portable emission measurement system - Chunying Lu; Shuwei Dong; Shanqian Huang; Shuohan Gao; Jinsheng Fu; Xinyi Tian; Sha Lin; Xinzhu Xiong; Xinjun Wang; Xinfeng Wang (Air Quality, Atmosphere & Health, 2025)

High-throughput screening of combined toxicity of nanoplastics and coexisting pollutants using luminescent bacterium - Xinyi Liao; Zhihao Xue; Yunbu Dai; Jie Hou; Daohui Lin; Luqing Zhang (NanoImpact, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Triflumezopyrim-induced changes in the flight ability and energy metabolism of the brown planthopper, Nilaparvata lugens - Jitong Li; Lei Zhu; Xinyi Lv; Xin Zhou; Xinyan Liang; Yiping Wang; Lin Chen; Jinglan Liu (Pesticide Biochemistry and Physiology, 2025)

Baicalin alleviates lipid accumulation in adipocytes via inducing metabolic reprogramming and targeting Adenosine A1 receptor - Zaikuan Zhang; Runzhi Wang; Jin Cai; Xinyi Li; Xiaosong Feng; Shengming Xu; Zhihong Jiang; Peiyi Lin; Zengyi Huang; Yajun Xie (Toxicon, 2025)

Microplastics enhance laccase-driven bisphenol A removal in multipollutant wastewater - Jie Zhang; Jiongna Liu; Xinyi Liu; Yu Su; Chunyang Yu; Xuemei Tan; Lin Zhuo; Mei Ye; Qinglin Luo; Biao Li (Journal of Environmental Management, 2025)

NIR-activated endoplasmic reticulum stress amplifier to regulate phagocytosis for macrophage-mediated cancer immunotherapy - Yaru Zhang; Wenyu Xie; Jiamin Luo; Rui Gao; Zhimin Gao; Xinyi Wang; Yongxin Huang; Chen Lin; Meiling Tan; Zhiyao Hou (Chemical Engineering Journal, 2025)

Changes in fertility and microbial communities of red soil and their contribution to crop yield following long-term different fertilization - Haoran Mao; Ke Leng; Xinyi Chen; Jie Zhang; Kailou Liu; Yongxin Lin; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2025)

Anemarrhenae rhizoma combined with Trichosanthis radix ameliorated type 2 diabetes in rats via the PI3K-Akt signalling pathway based on network pharmacology analysis - Yan Lin; Jinde Zheng; Xinyi Zhao; Bei Zheng; Ying Li; Wenjuan Yang; Bing Han; Hanxiao Tang; Meiling Zhang (Natural Product Research, 2025)

Enhancing rejection of short-chain per- and polyfluoroalkyl substances by tailoring the surface charge of nanofiltration membranes - Yue Zhi; Xiaoqing Zhao; Ao Shuai; Yonghui Jia; Xinyi Cheng; Shihong Lin; Feng Xiao; Le Han; Hongxiang Chai; Qiang He; Caihong Liu (Water Research, 2025)

The plant retromer components SNXs bind to ATG8 and CLASP to mediate autophagosome movement along microtubules - Yanglan Liao; Xibao Li; Wenlong Ma; Xinyi Lin; Jiayi Kuang; Xuanang Zheng; Zien Li; Fanfan Qiao; Chuanliang Liu; Jun Zhou; Faqiang Li; Ruixi Li; et al. (Molecular Plant, 2025)

Revealing future effectiveness of protected areas for biodiversity conservation in the Guangdong-Hong Kong-Macao Greater Bay Area - Fengze Lin; Mingjian Zhu; Xinyi Dong; Shiyu Ling; Bo Luan; Guoliang Pan (Landscape and Urban Planning, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

The response of chlorophyll a to nutrient and hydro-meteorological factors in Lake Taihu - Zhongtian Zhang; Hao Qin; Xinyi Wu; Qiang Xu; Xiaojing Wu; Lin Zhu; Jinge Zhu (Environmental Monitoring and Assessment, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

Blood cadmium levels of children aged 0–6 years in China: A national cross-sectional study - Xinxin Zhang; Yin Lin; Yuqing Wang; Junxia Liu; Xinyi Cui; Yong Chen; Yan Wu; Fengxiu Ouyang; Xianting Jiao; Kang Cai; Chonghuai Yan (Science of The Total Environment, 2025)

Effect of pectin with different esterification degree on the freeze-thaw stability of gluten protein: Structures, functional properties, and Cryoprotective mechanism - Wei Tang; Xinyi Lin; Longfei Ye; Jianfei He; Zhijun Wang; Jianfei Tang; Jianhua Liu; Peicheng Zhao (Food Chemistry, 2025)

Supramolecular deep eutectic solvents as green media for efficient extraction of tea polyphenols and its application in bio-active film - Dongting Huang; Lirong Chen; Xiaofen Chen; Xinyi Huang; Yourui Yang; Jian Liu; Yu Lin; Yongjing Liu; Hua Li (Food Chemistry, 2025)

Insomnia in Parkinson’s Disease: Causes, Consequences, and Therapeutic Approaches - Xiaoyu Duan; Hanshu Liu; Xinyu Hu; Qinwei Yu; Guiying Kuang; Long Liu; Shurui Zhang; Xinyi Wang; Jingwen Li; Danfang Yu; Jinsha Huang; Tao Wang; et al. (Molecular Neurobiology, 2025)

Isolation and characterization of high ammonium tolerant Fasciculochloris sp. HDMA-06 and its potential for nutrient removal and biodiesel production in simulated swine wastewater - Han Wang; Xinyi Wang; Jixin Liu; Yimeng Lin; Jingping Ge; Wenxiang Ping (Journal of Water Process Engineering, 2025)

Virus-bacterium interaction involved in element cycles in biological treatment of coking wastewater - Zhijie Tan; Wenli Chen; Xinyi Wei; Zhaoji Qiu; Weixiong Zhuang; Baoshan Zhang; Junting Xie; Yuexia Lin; Yuan Ren; Sergei Preis; Chaohai Wei; Shuang Zhu (Bioresource Technology, 2025)

The importance of porewater exchange process on carbon lateral export from saltmarsh creek to coastal sea - Jian’an Liu; Xueqing Yu; Xinyi Lin; Tong Peng; Liming Xue; Jinzhou Du (Journal of Oceanology and Limnology, 2025)

Correction: MFG-E8 Ameliorates Nerve Injury-Induced Neuropathic Pain by Regulating Microglial Polarization and Neuroinflammation via Integrin β3/SOCS3/STAT3 Pathway in Mice - Longqing Zhang; Xinyi Dai; Danyang Li; Jiayi Wu; Shaojie Gao; Fanhe Song; Lin Liu; Yaqun Zhou; Daiqiang Liu; Wei Mei (Journal of Neuroimmune Pharmacology, 2024)

Numerical Simulation of Hydrodynamic Performance of an Offshore Oscillating Water Column Wave Energy Converter Device - Peng Tang; Xinyi Lin; Wei Wang; Hongsheng Zhang (Journal of Marine Science and Engineering, 2024)
Wave energy, as a renewable energy source, plays a significant role in sustainable energy development. This study focuses on a dual-chamber offshore oscillating water column (OWC) wave energy device and performs numerical simulations to analyze the influence of chamber geometry on hydrodynamic characteristics and wave energy conversion efficiency. Unlike existing studies primarily focused on single-chamber configurations, the hydrodynamic characteristics of dual-chamber OWCs are relatively underexplored, especially regarding the impact of critical design parameters on performance. In this study, STAR-CCM+ V2302 software (Version 2410, Siemens Digital Industrial Software, Plano, TX, USA) is utilized to systematically evaluate the effects of key design parameters (including turbine configuration, mid-wall draught depth, and wall angles) on the hydrodynamic performance, wave energy capture efficiency, and wave reflection and loading characteristics of the device. The findings aim to provide a reference framework for the optimal design of dual-chamber OWC systems. The results show that the dual-chamber, dual-turbine (2C2T) configuration offers a 31.32% improvement in efficiency compared to the single-chamber, single-turbine (1C1T) configuration at low wave frequencies. In terms of reducing wave reflection and transmission, the 2C2T configuration outperforms the dual-chamber, single-turbine configuration. When the wall angle increases from 0° to 40°, the total efficiency increases by 166.37%, and the horizontal load decreases by 20.05%. Additionally, optimizing the mid-wall draught depth results in a 9.6% improvement in efficiency and a reduction of vertical load by 11.69%.

Microbial rrn copy number is associated with soil C: N ratio and pH under long-term fertilization - Xiu Wang; Jiahui Lin; Xinyi Peng; Yifan Zhao; Haodan Yu; Kankan Zhao; Albert Barberán; Yakov Kuzyakov; Zhongmin Dai (Science of The Total Environment, 2024)

An effective way to monitor the population of juvenile horseshoe crabs in the Beibu Gulf of China - Mujiao Xie; Yuyuan Bao; Xiaoyong Xie; Wuying Lin; Xiaohai Chen; Xinyi Zhao; Xiaobo Xiao (Regional Studies in Marine Science, 2024)

Effects of thermal oxidation interaction via various polar lipid and myofibrillar proteins on the aroma formation in large yellow croaker - Tingting Zhang; Ke Zhang; Xinyi Qi; Sijia Lin; Lei Qin; Xuhui Huang (Food Bioscience, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Functional connectivity of EEG motor rhythms after spinal cord injury - Jiancai Leng; Xin Yu; Chongfeng Wang; Jinzhao Zhao; Jianqun Zhu; Xinyi Chen; Zhaoxin Zhu; Xiuquan Jiang; Jiaqi Zhao; Chao Feng; Qingbo Yang; Jianfei Li; et al. (Cognitive Neurodynamics, 2024)

MFG-E8 Ameliorates Nerve Injury-Induced Neuropathic Pain by Regulating Microglial Polarization and Neuroinflammation via Integrin β3/SOCS3/STAT3 Pathway in Mice - Longqing Zhang; Xinyi Dai; Danyang Li; Jiayi Wu; Shaojie Gao; Fanhe Song; Lin Liu; Yaqun Zhou; Daiqiang Liu; Wei Mei (Journal of Neuroimmune Pharmacology, 2024)

A Siglec3-like lectin from Nile tilapia (Oreochromis niloticus): Transcriptional profiling upon Streptococcus agalactiae infection and its potential role in immune escape - Tingyun Zhang; Qiuxu Chen; Jingyi Chen; Yang Lei; Xinyi Liang; Xiayi Wei; Li Lin; Jianmin Ye; Meng Chen (Aquaculture, 2024)

AlphaFold-guided redesign of a plant pectin methylesterase inhibitor for broad-spectrum disease resistance - Yeqiang Xia; Guangzheng Sun; Junhua Xiao; Xinyi He; Haibin Jiang; Zhichao Zhang; Qi Zhang; Kainan Li; Sicong Zhang; Xuechao Shi; Zhaoyun Wang; Lin Liu; et al. (Molecular Plant, 2024)

Evaluation of the expression stability of potential reference genes for RT-qPCR in Spodoptera frugipreda larvae exposed to camptothecin - Yuting Huang; Xuanyue Yu; Xinyi Xie; Cuiting Liu; Huijiao Zhang; Jiaxiang Yuan; Jintian Lin; Benshui Shu; Jingjing Zhang (Journal of Asia-Pacific Entomology, 2024)

Dietary fiber modification: structure, physicochemical properties, bioactivities, and application—a review - Wei Tang; Xinyi Lin; Noman Walayat; Jianhua Liu; Peicheng Zhao (Critical Reviews in Food Science and Nutrition, 2024)

Enhancing extracellular monascus pigment production in submerged fermentation with engineered microbial consortia - Song Zhang; Meng Shu; Zihan Gong; Xinyi Liu; Chenyu Zhang; Ying Liang; Qinlu Lin; Bo Zhou; Ting Guo; Jun Liu (Food Microbiology, 2024)

Sulfur and phosphorus co-doped FeCoNiCrMn high-entropy alloys as efficient sulfion oxidation reaction catalysts enabling self-powered asymmetric seawater electrolysis - Zhipeng Yu; Danil W. Boukhvalov; Hao Tan; Dehua Xiong; Chuangshi Feng; Jingwei Wang; Wei Wang; Yang Zhao; Kaiyang Xu; Weifeng Su; Xinyi Xiang; Fei Lin; et al. (Chemical Engineering Journal, 2024)

The sensing of circRNA with tetrahedral DNA nanostructure modified microfluidic chip - Shiliang He; Lei Chen; Zhuolang Chen; Guihao Zhang; Yongjin Huang; Huaxiao Zheng; Qing Yang; Zhuoxi Mo; Xinyi Lin; Jiancheng Wen (Analytica Chimica Acta, 2024)

Temperature distribution evolution in zero-gap alkaline water electrolyzer: Experimental and modeling - Mengfei Zhang; Lingyu Gao; Lin Yang; Guixuan Shan; Yuxuan Wang; Xinyi Huo; Wei Li; Jinli Zhang (Fuel, 2024)

Grey-box modeling for thermal dynamics of buildings under the presence of unmeasured internal heat gains - Xinyi Lin; Zhe Tian; Wenjie Song; Yakai Lu; Jide Niu; Qiang Sun; Yanan Wang (Energy and Buildings, 2024)

Matrine induces cardiotoxicity by promoting ferroptosis through the Nrf2 antioxidant system in H9c2 cells - Xi Wang; Zixiong Lin; Xinyi Tang; Minjuan Xie; Ting Li; Jie Zhou (Toxicology Letters, 2024)

Temporal dynamics of rhizosphere bacterial community in the Robinia pseudoacacia–Mesorhizobium loti symbiotic system for remediation of cadmium-contaminated soils - Le Yang; Xing Ma; Jing Wang; Kang Zhang; Zhen Yang; Jiajia Li; Xinyi Liu; Pengyue Wu; Yanbing Lin; Zhouping Shangguan; Miaochun Fan (Applied Soil Ecology, 2024)

Landscape of plasmids encoding β-lactamases in disinfection residual Enterobacteriaceae from wastewater treatment plants - Zejun Lin; Zhenchao Zhou; Xinyi Shuai; Guangshu Zeng; Ruiqi Bao; Hong Chen (Water Research, 2024)

Unraveling the ecological mechanisms of Aluminum on microbial community succession in epiphytic biofilms on Vallisneria natans leaves: Novel insights from microbial interactions - Xue Peng; Xiaowen Zhang; Zhuxi Li; Shuxian Zhang; Xinyi Zhang; Haokun Zhang; Qingwei Lin; Xia Li; Lu Zhang; Fangjie Ge; Zhenbin Wu; Biyun Liu (Journal of Hazardous Materials, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Characterizing sedimentary black carbon in the Pearl River Estuary, Southern China - Xinyi Liu; Yali Li; Tian Lin; Nairong Guo; Jiawen Yuan; Ying Yang; Wei-dong Zhai (Marine Chemistry, 2024)

Ranking the risk of antibiotic resistance genes by metagenomic and multifactorial analysis in hospital wastewater systems - Xinyi Shuai; Zhenchao Zhou; Lin Zhu; Chioma Achi; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Yanhan Lin; Hong Chen (Journal of Hazardous Materials, 2024)

3D/2D MnO/MXene heterostructure with high efficiency for adsorbing uranium - Chao Zhang; Yi Wang; Yi-Lin Liu; Qingming Zeng; Yanjun Wen; Lulin Guo; Haodong Chen; Xinyi Xie; Qingyi Zeng (Chemical Engineering Journal, 2024)

Insights into the enhanced mechanism of electron beam pretreatment on application performance for poly (butylene adipate-co-terephthalate)/acetylated cellulose composite plastics - Li Niu; Xinyi He; Xiuyun Zhang; Wei Liang; Qian Lin; Wenhao Li (Carbohydrate Polymers, 2024)

Chemical composition, sources, and processes of winter haze in Chengdu, China: Insights from integrating the bulk chemical and single particle approaches - Junke Zhang; Wei Sun; Yunfei Su; Xiaoxue Peng; Chunying Chen; Xinyi Fu; Yuhan Long; Gehui Wang; Zhihan Rao; Lin Han; Xiaojuan Huang (Atmospheric Environment, 2024)

Antibiotic resistance genes alterations in murine guts microbiome are associated with different types of drinking water - Zhenchao Zhou; Zejun Lin; Xinyi Shuai; Chioma Achi; Hong Chen (Journal of Hazardous Materials, 2024)

The adsorption and release mechanism of different aged microplastics toward Hg(II) via batch experiment and the deep learning method - Lianghong Li; Bin Xue; Haiying Lin; Wenlu Lan; Xinyi Wang; Junqi Wei; Mingen Li; Mingzhi Li; Yu Duan; Jiatong Lv; Zixuan Chen (Chemosphere, 2024)

Sorting Technology for Mesenchymal Stem Cells from a Single Tissue Source - Xinyi Feng; Fangfang Qi; Hailin Wang; Wenzhen Li; Yuyang Gan; Caiyu Qi; Zhen Lin; Lu Chen; Piao Wang; Zhiqi Hu; Yong Miao (Stem Cell Reviews and Reports, 2024)

Genome-wide DNA methylation of lesional and peri-lesional skin in vitiligo: a comparative and integrated analysis of multi-omics in Chinese population - Lin Liu; Yuzhou Xue; Yuxin Li; Yangmei Chen; Xingyu Pan; Yujing Huang; Tingqiao Chen; Judan Zhong; Xinyi Shao; Yihuan Pu; Jin Chen (Human Genetics, 2024)

Single-cell lineage tracing with endogenous markers - Yan Xue; Zezhuo Su; Xinyi Lin; Mun Kay Ho; Ken H. O. Yu (Biophysical Reviews, 2024)
Resolving lineage relationships between cells in an organism provides key insights into the fate of individual cells and drives a fundamental understanding of the process of development and disease. A recent rapid increase in experimental and computational advances for detecting naturally occurring somatic nuclear and mitochondrial mutation at single-cell resolution has expanded lineage tracing from model organisms to humans. This review discusses the advantages and challenges of experimental and computational techniques for cell lineage tracing using somatic mutation as endogenous DNA barcodes to decipher the relationships between cells during development and tumour evolution. We outlook the advantages of spatial clonal evolution analysis and single-cell lineage tracing using endogenous genetic markers.

Framing seascape connectivity modeling to prioritize marine conservation effort in China’s coastal sea - Yiyang Kang; Yuxuan Lin; Zhixue Chen; Xinyi Zhang; Yi Li (Frontiers in Marine Science, 2024)
Anthropogenic disturbances and climate change are projected to become leading drivers of biodiversity loss and ecological connectivity degradation in marine ecosystems. However, the lack of quantitative understanding for seascape connectivity modeling hinders our ability in providing large-scale marine conservation guidance. By applying well-established theories and tools in landscape connectivity study and marine-specific indicators, we proposed a framework to evaluate the resistance-based seascape connectivity among marine habitats and Marine Protected Areas (MPAs) across China’s coastal sea. The spatial vulnerability of marine habitats was further assessed to prioritize conservation effort. Our results showed that 82% of China’s coastal seas were covered with middle to high level of resistance for migratory marine species, mainly due to concentrated inshore anthropogenic disturbances such as ship traffic and ocean pollution. With the modeled migration distances of different species guilds from short-range (25 km) to long-range (100 km), the area percentage of connected corridors increased from 12.02% to 44.68% in the study area. Vulnerable areas were identified as high resistance (high exposure) and abundant threatened species (high sensitivity) but with small number of connected corridors (low adaptive capacity), primarily distributed in offshore regions of Yellow Sea and East China Sea. Collectively, inshore regions with high anthropogenic disturbances warrant regulation and mitigation in major coastal cities and ports. While the lack of interconnected networks for offshore regions prioritized efforts to enhance seascape connectivity through the establishment of MPA network. Sensitive species groups require more attention in future marine conservation, including threatened populations, climate refugees of marine species, and species with limited movement ranges. This study highlights the potential of developing seascape connectivity model based on landscape theories, and the importance of seascape connectivity study in guiding evidence-based marine conservation strategies.

Bacteriophages: Vectors of or weapons against the transmission of antibiotic resistance genes in hospital wastewater systems? - Xinyi Shuai; Zhenchao Zhou; Xiaoliang Ba; Yanhan Lin; Zejun Lin; Zhe Liu; Xi Yu; Jinyu Zhou; Guangshu Zeng; Ziye Ge; Hong Chen (Water Research, 2024)

Water stress significantly affects the diurnal variation of solar-induced chlorophyll fluorescence (SIF): A case study for winter wheat - Jingyu Lin; Litao Zhou; Jianjun Wu; Xinyi Han; Bingyu Zhao; Meng Chen; Leizhen Liu (Science of The Total Environment, 2024)

Host plant-induced changes in metabolism and osmotic regulation gene expression in Diaphorina citri adults - Benshui Shu; Xinyi Xie; Jinghua Dai; Luyang Liu; Xueming Cai; Zhongzhen Wu; Jintian Lin (Journal of Insect Physiology, 2024)

Do different types of urban streets lead to varying COVID-19 risk perceptions? An empirical study from a spatial heterogeneity perspective - Yongqi Hou; Chongxian Chen; Xiaoling Lin; Zhitong Zhang; Xinyi Liu; Jiehang Xie; Shaoping Guan (Environmental Impact Assessment Review, 2024)

Emerging and legacy perfluoroalkyl and polyfluoroalkyl substances (PFAS) in surface water around three international airports in China - Jing Liu; Zhen Zhao; Jie Li; Xia Hua; Boxuan Zhang; Caijun Tang; Xinyi An; Tian Lin (Chemosphere, 2023)

Distribution heterogeneity of sediment bacterial community in the river-lake system impacted by nonferrous metal mines: Diversity, composition and co-occurrence patterns - Aihua Wang; Mengchang He; Huiji Liu; Wei Ouyang; Xinyi Liu; Qin Li; Chunye Lin; Xitao Liu (Environmental Pollution, 2023)

The longitudinal association between indoor air pollution and sarcopenia in China: the mediating role of depression - Miyuan Wang; Lin Hu; Hongye Peng; Junjie Yao; Xinyi Zhang; Zheng Zhang (Environmental Science and Pollution Research, 2023)

Microbial electrolysis cell simultaneously enhancing methanization and reducing hydrogen sulfide production in anaerobic digestion of sewage sludge - Xiangyu Chen; Benyi Xiao; Xinyi Tang; Chunlin Bian; Junxin Liu; Lin Li (Chemosphere, 2023)

Selected rhizobacteria facilitated phytoremediation of barren and heavy metal contaminated gold mine tailings by Festuca arundinacea - Xu Chen; Chaoyu Sun; Qian Zhang; Xinyi Jiang; Chenjing Liu; Hai Lin; Bing Li (Chemosphere, 2023)

A new model to accurately measure the radon exhalation rate from soil using AlphaGUARD - Shuaibin Liu; Tao Hu; Fen Lin; Zhongkai Fan; Ruomei Xie; Shuai Yuan; Jiulin Wu; Haibo Yi; Yixiang Mo; Jiale Sun; Linquan Chen; Huiying Li; et al. (Journal of Environmental Radioactivity, 2023)

Association of greenness surrounding school with aggression among adolescents: A multi-site study in China - Yi Zhang; Yanqi Li; Xinyi Xie; Xiaoyi Lin; Mengxin Huang; Huihang Fu; Weiju Zhou; John S. Ji; Yizhen Yu; Jie Tang (Environmental Research, 2023)

Development of a recurrent spatiotemporal deep-learning method coupled with data fusion for correction of hourly ozone forecasts - Jie Li; Ji-cheng Jang; Yun Zhu; Che-Jen Lin; Shuxiao Wang; Jia Xing; Xinyi Dong; Jinying Li; Bin Zhao; Bingyao Zhang; Yingzhi Yuan (Environmental Pollution, 2023)

Load extraction from actual operation data for data-driven ultra-short-term room air-conditioning load prediction - Zhe Tian; Wenjie Song; Yakai Lu; Xinyi Lin; Jide Niu (Energy and Buildings, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Fatigue at sea during and after the COVID-19 pandemic: A comparative study of two matched samples of seafarers - Zhiwei Zhao; Lijun Tang; Yunlei Ma; Yueyan Wu; Shiqi Lin; Zefan Wu; Zheng Zhou; Xinyi Wang; Xinjian Wang (Marine Policy, 2023)

Preparation, chemical composition, glycolipid-lowering activity and functional property of high-purity polysaccharide from Moringa oleifera Lam. leaf: A novel plant-based functional hydrophilic colloid - Xinyi Yang; Lianzhu Lin; Mouming Zhao (Food Hydrocolloids, 2023)

Electron structure and defect co-modulation to boost zinc storage performance of urchin-like VS4-based microspheres as advanced cathodes for aqueous Zn-ion batteries - Xinyi Zhou; Yuanxia Li; Ji Chen; Qiaoji Zheng; Yu Huo; Fengyu Xie; Dunmin Lin (Chemical Engineering Journal, 2023)

Estimating the effect of increasing ambient temperature on antimicrobial resistance in China: A nationwide ecological study with the difference-in-differences approach - Weibin Li; Chaojie Liu; Hung Chak Ho; Lin Shi; Yingchao Zeng; Xinyi Yang; Haohai Xia; Wangjian Zhang; Cunrui Huang; Lianping Yang (Science of The Total Environment, 2023)

Imbalanced data-oriented model learning method for ultra-short-term air conditioning load prediction - Zhe Tian; Xinyi Lin; Yakai Lu; Wenjie Song; Jide Niu (Energy and Buildings, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Reversal of soil moisture constraint on vegetation growth in North China - Ruohua Du; Jianjun Wu; Feng Tian; Jianhua Yang; Xinyi Han; Meng Chen; Bingyu Zhao; Jingyu Lin (Science of The Total Environment, 2023)

Exploring key physicochemical sediment properties influencing bioleaching of heavy metals - Chuncheng Wu; Xinyi Hu; Haizhen Wang; Qi Lin; Chaofeng Shen; Liping Lou (Journal of Hazardous Materials, 2023)

Covalent modification of soy protein hydrolysates by EGCG: Improves the emulsifying and antioxidant properties - Tianyi Wu; Ling Lin; Xinyi Zhang; Xinyue Wang; Jian Ding (Food Research International, 2023)

Programmable CRISPR-Cas12a and self-recruiting crRNA assisted dual biosensing platform for simultaneous detection of lung cancer biomarkers hOGG1 and FEN1 - Xia Cheng; Xinyi Xia; Dandan Ren; Qiutong Chen; Guanhong Xu; Fangdi Wei; Jing Yang; Lin Wang; Qin Hu; Jianjun Zou; Yao Cen (Analytica Chimica Acta, 2023)

Continuous inactivation of human adenoviruses in water by a novel g-C3N4/WO3/biochar memory photocatalyst under light-dark cycles - Chi Zhang; Wei Xiong; Yi Li; Li Lin; Xinyi Zhou; Xinyan Xiong (Journal of Hazardous Materials, 2023)

Effects of ultrasonic treatment on the surface bacteria of Lyophyllum decastes during storage - Yuxin Hu; Xiaotong Lin; Xinrui Liu; Xinyi Zhong; Hailu Lin; Danxia Jiang; Fangyi Zhang; Xinlin Zhong; Yuji Jiang; Bingzhi Chen (Food Research International, 2023)

Water mass-driven multiple ecological effects determine the biodiversity and community assembly of microbial flagellates in subtropic-tropic marginal seas of China - Xin Guo; Qiang Liu; Xiaoqing Lin; Xinyi Zheng; Cheng Huang; Mengwen Pang; Lingfeng Huang (Estuarine, Coastal and Shelf Science, 2023)

Electricity consumption and load prediction method for Chinese rural residences based on the randomness and seasonality in electricity usage behavior - Pengli Yuan; Lin Duanmu; Zongshan Wang; Ke Gao; Xinyi Zhao; Xintong Liu; Weihong Kong (Energy and Buildings, 2023)

Two silver energetic coordination polymers based on a new N-amino-contained ligand: Towards good detonation performance and excellent laser-initiating ability - Qing Lang; Xinyi Li; Jianxin Zhou; Yuangang Xu; Qiuhan Lin; Ming Lu (Chemical Engineering Journal, 2023)

Effects of Spartina alterniflora Invasion and Mangrove Restoration on Soil Microbial Functional Diversity - Yongni He; Genmei Lin; Xinyi Gao; Yiting Cao; Naxu Hu; Rui Li; Jianxiang Feng (Journal of Soil Science and Plant Nutrition, 2022)

Inhibition of cGAS in Paraventricular Nucleus Attenuates Hypertensive Heart Injury Via Regulating Microglial Autophagy - Chengzhi Han; Xinyi Qian; Xiaorong Ren; Shutian Zhang; Li Hu; Jingyao Li; Yijun Huang; Renhui Huang; Kokwin Ooi; Hong Lin; Chunmei Xia (Molecular Neurobiology, 2022)

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Coupling effects of hydrological characteristics and nutrient load in sediments on the trophic state of reservoirs - Fan Xinyi; Yue Yihong; Mei Lin; Li Xiaoying; Hu Zhehui; Luo Jiajie; Liu Liu; Wang Fushun (Acta Geochimica, 2021)

The Potential of Constructed Wetland Plants for Bioethanol Production - Yan Lin; Yafang Zhao; Xinyi Ruan; Tyler J. Barzee; Zhenyu Zhang; Hainan Kong; Xiaoling Zhang (BioEnergy Research, 2020)

Fine mapping, candidate genes analysis, and characterization of a brown planthopper (Nilaparvata lugens Stål) resistance gene in the rice variety ARC5984 - Jiebin Lin; Xinyi Wang; Yang Li; Fanggui Bi; Ling Cheng; Fengkuang Huang; Rongbai Li; Yongfu Qiu (Euphytica, 2020)

Genomic and Allelic Analyses of Laccase Genes in Sugarcane (Saccharum spontaneum L.) - Wenping Zhang; Jishan Lin; Fei Dong; Qing Ma; Songlin Wu; Xinyi Ma; Mahpara Fatima; Haifeng Jia; Ray Ming (Tropical Plant Biology, 2019)

The associations of air pollution exposure during pregnancy with fetal growth and anthropometric measurements at birth: a systematic review and meta-analysis - Li Fu; Yi Chen; Xinyi Yang; Zuyao Yang; Sha Liu; Lei Pei; Baixiang Feng; Ganxiang Cao; Xin Liu; Hualiang Lin; Xing Li; Yufeng Ye; et al. (Environmental Science and Pollution Research, 2019)

Comparison and evaluation of uncertainties in extreme flood estimations of the upper Yangtze River by the Delta and profile likelihood function methods - Jianhua Wang; Fan Lu; Kairong Lin; Weihua Xiao; Xinyi Song; Yanhu He (Stochastic Environmental Research and Risk Assessment, 2017)

A review of soil cadmium contamination in China including a health risk assessment - Lin Wang; Xiangfen Cui; Hongguang Cheng; Fei Chen; Jiantong Wang; Xinyi Zhao; Chunye Lin; Xiao Pu (Environmental Science and Pollution Research, 2015)

Temperature anomalies in central and eastern Tibetan Plateau in relation to general circulation patterns during 1951-1993 - Zhi-Yong Yin; Zhenyao Lin; Xinyi Zhao (International Journal of Climatology, 2000)